If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0 = 3(2x + 4) Reorder the terms: 0 = 3(4 + 2x) 0 = (4 * 3 + 2x * 3) 0 = (12 + 6x) Solving 0 = 12 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 0 + -6x = 12 + 6x + -6x Remove the zero: -6x = 12 + 6x + -6x Combine like terms: 6x + -6x = 0 -6x = 12 + 0 -6x = 12 Divide each side by '-6'. x = -2 Simplifying x = -2
| y=-3.5x-4.5 | | 6u-4u=10 | | 198=5x+3(-7x+2) | | (m=5)/5=3 | | 3x+25+-37=126 | | 44=2v | | -8x+5(2x-1)=4x+7 | | -4p+2+20p=15p+18 | | 7/m=3/9 | | 5+2(x+3)=11 | | y=-3.5-4.5 | | 3x-5(-x-17)=181 | | 198=5x+3(-7+2) | | 36/x=30/42 | | n/125=4/100 | | (4x)(-3xy^2)=-12x^2y^2 | | 45t+9= | | x=16+-0.4y | | 4c+19c+19=-20+20c | | 7x-2=5x-3+2x+1 | | c=1/2e*m | | .25x+.10y=4 | | 686=7(-8x-22) | | -3-16b=-3-15b-2b | | -x+6=y | | (3x-5)+(7y)=180 | | 6y=-2+3x | | -18w-17=19-20w | | 7x-2=5x-3+2x-1 | | -2*10-3y=-7 | | 17=3x-2(x-5) | | 2p+2p-3=2p+1 |